PERAN PENTING ETIKA BISNIS ISLAM TERHADAP PENDAPATAN DAN PENGEMBANGAN UMKM - Adek Safitri Nasution; M. Yarham (Prodi Perbankan Syariah UIN Sumatera Utara Medan, 2023)
Ethics is a scientific discipline that deals with the character, values, and norms of human behavior, be it commendable or disgraceful behavior depending on the person judging it. And what is meant by Islamic business ethics is the overall ethics that must be applied and become a guide for business people in accordance with sharia provisions or provisions from the Qur'an and hadith which are guidelines for Muslims and the words of the Prophet. Business people, especially Micro, Small and Medium Enterprises (MSMEs), Islamic business ethics is an effective way of developing and increasing income for those who own a business. Because there are already rules for doing business and developing a business. When a business actor can apply Islamic business ethics in running his business, it will make it easier to develop a business and easier to identify or fix if there is a problem in a business. The research method used by the author is a qualitative method and through literature reviews from books and journals that are relevant and recent. The results of this study prove that Islamic business ethics have several positive impacts and provide benefits to the income and development of Micro, Small and Medium Enterprises, for example, it is easier to run a business, be disciplined, orderly, and reduce the risks that will be faced in carrying out economic activities and are very profitable.